2022
DOI: 10.3389/fsurg.2022.882726
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Negative Pressure Suction Method Reduces the Incidence of PONV after Orthognathic Surgery

Abstract: ObjectiveTo investigate the effect of gastric negative pressure suction on the incidence of postoperative nausea and vomiting (PONV) in patients undergoing orthognathic surgery.MethodsA retrospective study of 772 patients who underwent orthognathic surgery from October 2016 to January 2021 was performed, excluding possible confounding factors. The patients were divided into a negative gastric suction group (group 1) and a group without gastric suction (group 2), according to whether gastric suction was used af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…These factors may cause bias and influence the reliability of the result. Furthermore, a retrospective study of Wang et al [ 57 ] analyzed 772 patients to discuss the relationship between gastric negative pressure suction and the incidence of PONV after orthognathic surgery. Their results revealed that the incidence of PONV was halved when patients received gastric negative pressure suction.…”
Section: Discussionmentioning
confidence: 99%
“…These factors may cause bias and influence the reliability of the result. Furthermore, a retrospective study of Wang et al [ 57 ] analyzed 772 patients to discuss the relationship between gastric negative pressure suction and the incidence of PONV after orthognathic surgery. Their results revealed that the incidence of PONV was halved when patients received gastric negative pressure suction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent retrospective study with a large-scale sample also determined its effects on reducing the incidence of POV and operation time in orthognathic surgery. [ 19 ] They declared that the clinical benefits of gastric aspiration were not only reflected in reducing POV but also may prevent POV from the original source, such as reducing the operation time. Another clinical observational investigation also supported the utilization of gastric aspiration in ear, nose, and throat surgery because of the lower incidence and severity of PONV after gastric aspiration application.…”
Section: Discussionmentioning
confidence: 99%
“…However, at the same time, indwelling gastric tubes may also stimulate the pharynx and larynx, although they are not a continuous catheterization in oral and maxillofacial surgery. [ 19 ] In addition, the method of gastric tube insertion could be another factor influencing POV. Erkalp et al argued that the orogastric method would be more effective than the nasogastric method due to easier and fewer pharyngology-related complications, which may be a potential interfering factor of POV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations